A A Cross-Sectional Study on Behaviour-Based Safety (Bbs) Among Workers in A Construction Site - Muhammad Multazam Mohd Nasir; Nurrul Hafeezah Binti Sahak; Baiyinah Binti Haji A. Talip (Progress in Engineering Application and Technology, 2023)
Malaysia’s new behavior-based safety (BBS) programme focuses on risky conduct. Malaysia’s building industry executed and sustained the initiative. This study identified behavior-based safety among construction employees at Package Bus Depot Serdang, found a correlation between general necessity for behavior-based safety and awareness of it, and suggested ways to improve implementation. Methodology: The cross-sectional study identified characteristics linked to behavior-based safety among workers at the Package Bus Depot Serdang building site (BDT202) by surveying relevant personnel. The questionnaire covers socio-demographic background, behavior-based safety awareness, and general equipment. August–November 2022 saw this study. Findings: The study analyses data and questionnaire survey results. The SPSS analysis and 100% respondent rate were the findings. Age, gender, status, education, weight, height, BMI, nationality, and race were analysed. Subsections described data normality test, descriptive analysis, reliability test, and Spearman correlation coefficient. General workers were 95% BBS-aware. The outcome suggests workers understand BBS.